2007
DOI: 10.5014/ajot.61.4.421
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Culture on Children’s Community Participation in Israel

Abstract: OBJECTIVE. This study compared the participation in activities outside of formal school among Jewish and Druze Israeli children. It also examined the impact of gender and the interaction of culture and gender on participation. METHODS. Participants included 30 Jewish and 30 Druze children ages 8–10 years, who completed the Children’s Assessment of Participation and Enjoyment (CAPE). RESULTS. On most of the scales measured, the Jewish children showed a significantly higher particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 24 publications
3
31
2
Order By: Relevance
“…Previous studies have highlighted the impact that both personal and environmental factors have on determining the activity participation patterns and preferences of typically developing children (Engel-Yeger et al, 2007;Engel-Yeger & Jarus, 2008). In the present study, significant differences between boys and girls were found in 3 of the 10 activity CAPE/PAC participation and preference scales.…”
Section: Impact Of Gender On Children's Participationcontrasting
confidence: 52%
See 1 more Smart Citation
“…Previous studies have highlighted the impact that both personal and environmental factors have on determining the activity participation patterns and preferences of typically developing children (Engel-Yeger et al, 2007;Engel-Yeger & Jarus, 2008). In the present study, significant differences between boys and girls were found in 3 of the 10 activity CAPE/PAC participation and preference scales.…”
Section: Impact Of Gender On Children's Participationcontrasting
confidence: 52%
“…Although previous research has provided some knowledge and understanding into the effect of the environment on the activity participation of children, much of this information has been established overseas and does not directly relate to the activity participation of Australian children (Engel-Yeger, Jarus, & Law, 2007). Australia is made up of three different primary geographic locations: urban, rural, and remote.…”
mentioning
confidence: 99%
“…In Israel, the tool was translated into Hebrew and Arabic. Previous studies have been performed with the CAPE in Israel, demonstrating that it is sensitive in distinguishing between different cultures (Engel-Yeger et al, 2007), between typical populations and distinguishing children with cerebral palsy (CP) (EngelYeger et al, 2009).…”
Section: Participantsmentioning
confidence: 99%
“…Participation and the factors that infl uence it create a complex set of relationships (Heah et al, 2007;King et al, 2006;Law et al, 2004). Culture, family, health status and contextual factors have been identifi ed as some of the main determinants of children's participation (Engel-Yeger et al, 2007;Law, 2002;King et al, 2003;Larson and Verma, 1999;Brown and Gordon, 1987).…”
Section: Introductionmentioning
confidence: 99%